2011
DOI: 10.1371/journal.pone.0028098
|View full text |Cite
|
Sign up to set email alerts
|

dp53 Restrains Ectopic Neural Stem Cell Formation in the Drosophila Brain in a Non-Apoptotic Mechanism Involving Archipelago and Cyclin E

Abstract: Accumulating evidence suggests that tumor-initiating stem cells or cancer stem cells (CSCs) possibly originating from normal stem cells may be the root cause of certain malignancies. How stem cell homeostasis is impaired in tumor tissues is not well understood, although certain tumor suppressors have been implicated. In this study, we use the Drosophila neural stem cells (NSCs) called neuroblasts as a model to study this process. Loss-of-function of Numb, a key cell fate determinant with well-conserved mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…A previous study showed that overexpression of p53 can suppress the supernumerary neuroblast phenotype induced by loss of numb function in the absence of caspase activation (Ouyang et al, 2011). This study also showed that co-expression of Cyclin E can abolish the suppressive effect of the overexpression of p53 on the supernumerary neuroblast phenotype in numb mutant clones.…”
Section: Activation Of Necrosis By a P53-dependent Mechanismsupporting
confidence: 57%
See 1 more Smart Citation
“…A previous study showed that overexpression of p53 can suppress the supernumerary neuroblast phenotype induced by loss of numb function in the absence of caspase activation (Ouyang et al, 2011). This study also showed that co-expression of Cyclin E can abolish the suppressive effect of the overexpression of p53 on the supernumerary neuroblast phenotype in numb mutant clones.…”
Section: Activation Of Necrosis By a P53-dependent Mechanismsupporting
confidence: 57%
“…Brain neuroblasts appear incapable of undergoing apoptosis during larval development as the Polycomb proteins actively silence the apoptotic genes (Bello et al, 2007;Siegrist et al, 2010). Consistently, overexpression of p53 reduces the total number of larval brain neuroblasts in the absence of caspase activation (Ouyang et al, 2011). Thus, fly larval brain neuroblasts provide a unique system for discovering genes that elicit an alternative cell death modality in a stem cell type that is apoptosis deficient.…”
Section: Introductionmentioning
confidence: 88%
“…The p53B isoform may also participate in other processes that Drosophila p53 has been implicated in, which include the culling of primordial germ cells, meiotic checkpoints, DNA repair, stem cell divisions, and tissue regeneration. 41,[60][61][62][63][64][65][66][67][68][69] Our results indicate that p53A and p53B localize to nuclear bodies and physically associate, an interaction that is likely direct through the conserved p53 oligomerization domain. Therefore, p53 tetramers may be heterogeneous and have different ratios of p53A and p53B subunits.…”
Section: Discussionmentioning
confidence: 64%
“…Other well-characterized human tumour suppressors, such as the kinase Lkb1 , whose loss-of-function phenotype results in Peutz-Jeghers syndrome, and p53, regulate cell polarity in worms, fl ies and humans and might be involved in asymmetric cell division as well (Marignani 2005 ;Cicalese et al 2009 ;Ouyang et al 2011b ). Thus, similar to the situation in Drosophila , asymmetric cell division in mammals appears to be involved in the regulation of stem and progenitor cell self-renewal, and the regulation of cell cycle progression and growth control.…”
Section: Growth and Proliferationmentioning
confidence: 99%